2019
DOI: 10.3390/recycling4020020
|View full text |Cite
|
Sign up to set email alerts
|

Coloured Plastic Bags for Kerbside Collection of Waste from Households—To Improve Waste Recycling

Abstract: Today, considerable amounts of resources are landfilled or incinerated, and recyclable materials such as metal, glass, plastic, and paper are disposed of as residual waste instead of being sorted into recyclable fractions. Recycling is one way of transitioning towards a circular economy and a more resource-efficient society. However, in many older cities there is insufficient space for waste bins, which makes waste sorting difficult. The aim of the study was to test how the introduction of a new kerbside colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, 3D printing can incorporate raw materials effectively in a way that can reduce waste and conserve energy. Additionally, since household waste accounts for at least 31% of the residual waste, 3D printing can include recycling systems at a household-scale level which can be considered as a good alternative to centralize the recycling [1,38].…”
Section: Introductionmentioning
confidence: 99%
“…However, 3D printing can incorporate raw materials effectively in a way that can reduce waste and conserve energy. Additionally, since household waste accounts for at least 31% of the residual waste, 3D printing can include recycling systems at a household-scale level which can be considered as a good alternative to centralize the recycling [1,38].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the morphology of solid waste in Sweden showed that about 31-36% is plastic packaging and paper that has not been sorted [9,10]. Thus, there is great potential for reducing tailings and sorting packaging and food waste.…”
Section: Research Methodology and Sources Of Informationmentioning
confidence: 99%
“…Once the Tc, Tg, and Tm values are determined, the range of processing temperatures can be identified, providing a reasonable estimation of the suitability of the materials for industrial applications. The most common industrial processing temperature is ±40 °C [46,49]. In addition, when the Tc and Tm values of the materials are known, the enthalpies of the materials can be estimated, providing an understanding regarding how much energy and heat would be required in the manufacturing process for such composite materials, which is an important consideration from the industrial manufacturing per- The obtained DSC data were used to characterize the intrinsic thermal properties of the materials.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…Fortunately, 3D printing can also be performed using waste raw materials, effectively conserving energy. A more centralized recycling approach could benefit from the usage of 3D printing technology because household waste constitutes approximately 31% of the residual waste [ 1 , 46 ]. Moreover, the waste of 3D printed composite material can also be easily recycled, making this method an eco-friendly disposal method as well for a wide range of composites [ 37 ].…”
Section: Introductionmentioning
confidence: 99%